A stressing method for producing high-density Trichoderma spores in a dual-layer by utilizing a starch-based medium in a reconditioning approach. (September 2022) - Abuhena, Md.; Kabir, Md. Golam; Azim, Md. Faisal; Al-Rashid, Jubair; Rasul, Noorain Munim; Huq, Md. Amdadul
Abstract: A stressing method was adopted to produce Trichoderma harzianum TI21 spores in a dual-layer with an outer-layer spore free of media-residue by reconditioning the starch-based rice agar medium. The essential parameters were explored and optimized using statistical methods. The single factorial test's findings demonstrated that lower-pH and starch-based media encouraged sporulation while suppressing the growth of contaminants. The Box-Behnken design identified the ideal levels as pH 4, 30 °C, and 75 %. In the reconditioning approach, the first harvest produced 4.91 (3.64 × 10 11  CFU/g) of spores (g/L) after 5 days of cultivation, while the second and third harvests produced 4.19 and 3.48 (respectively) after 4 days of cultivation, leaving 755 (g/L) (2.25 × 10 10  CFU/g) media-mixed spores. As compared to media-mixed spores, media residue-free spores had significantly longer viability (18 months) with no clogging hazards. According to the findings, the method can be used industrially to produce stable, high-density spores for widespread agricultural applications. Graphical abstract: Sporulation of Trichoderma harzianum TI21 in a reconditioning approach on starch-based media in the stressing method. Unlabelled Image Highlights: Production technology reduced the cultivation time. Rice agar and low pH suppressed the growth of contaminants. Box-Behnken design is effective for predicting the spore yield. Reconditioning approach maximized the yield of media-free high-density spores. Media-free spores showed longer viability with no clogging effects.